The Rise of the Anthroposphere since 50,000 Years: An Ecological Replacement of Megaherbivores by Humans in Terrestrial Ecosystems? - Bocherens, Hervé (Frontiers in Ecology and Evolution, 2018)
Megaherbivores fulfilled a number of important ecological functions in terrestrial ecosystems and behaved as ecological engineers since 300 million years until around 12,000 years ago. These essential ecological functions include opening vegetation cover, selective seed dispersal and nutrient recycling and spreading. Thanks to these effects, megaherbivores change the vegetation structure where they live, with cascading effects on smaller herbivores and also on climate. The late Pleistocene extinction strongly impacted the megaherbivores almost all over the world and led to the loss of these important ecological functions in terrestrial ecosystems. These functions were partially restored by agriculturist humans through an ecological replacement that occurred through an ecological shift within the species Homo sapiens. A better understanding of the differences and similarities between the ecological impacts of megaherbivores and those of agricultural humans should help to predict the future of terrestrial ecosystems.